2013
DOI: 10.3944/aott.2013.2669
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pronation and inclination on the measurement of the hallucal distal metatarsal articular set angle

Abstract: According to the current data, the measurement of DMAA is not suitable for making clinical and surgical decisions. The inclination of the first metatarsal can change, depending on the height of the medial longitudinal arch. By doing this study, we are trying to simulate the pes cavus and pes planus deformity on the radiologic measurement of pronation of the hallux. According to our results, inclination has no effect on the measurement of DMAA. However, the measurement of DMAA is expected to be dependent on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…We did not obtain DMAA data, as we met the ±3°diversity range between different researchers. This observation is similar to that in number of independent studies [22][23][24].…”
Section: Discussionsupporting
confidence: 79%
“…We did not obtain DMAA data, as we met the ±3°diversity range between different researchers. This observation is similar to that in number of independent studies [22][23][24].…”
Section: Discussionsupporting
confidence: 79%
“…These investigations elucidating the relationships between the coronal, transverse, and sagittal dimensions of HV allow a thorough understanding of this deformity as a multiplanar process. In our systematic review, we identified 26 studies that reported on the significance between M1 pronation and the M1-M2 intermetatarsal angle (IMA), 9,13,16,18,29,30,33,35,45,57,67,70,74 hallux valgus angle (HVA), 9,13,16,18,21,45,67,70,74 distal metatarsal articular angle (DMAA), 8,15,16,18,19,33,65,84 lateral metatarsal head shape, 16,20,58,97,98 and sesamoid position. 13,16,18,20,21,45,74,80 However, because of the heterogeneity of these inclusions (eg, various measurement methods and formatting of reported data), we could not perform a meaningful statistical meta-analysis.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…As this variable is defined by its representation of the distal articular surface orientation, it has been heavily scrutinized as being solely a radiographic artifact of M1 rotation, rather than an independent measure of dysplasia. 8,15,16,18,19,33,65,84…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…11,12,36 The measured interobserver reliability is poor, 2,7,18 especially when there is an M1 pronation component. 1,9,13,32,37 First metatarsal lateral inclination or plantarflexion seems to also influence this measurement. 32 Some authors have questioned the existence of an increased valgus deformity of distal articular surface of M1 in HV.…”
Section: Introductionmentioning
confidence: 97%